2015
DOI: 10.1007/s00428-015-1827-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression of miRNAs in adenoid cystic carcinomas of the breast and salivary glands

Abstract: Despite their similar histomorphologic appearance, adenoid cystic carcinomas of the breast and salivary glands (bACCs and sACCs, respectively) are clinically and pathologically diverse. We studied the expression levels of 18 microRNAs (miRNAs) in bACCs and sACCs and control normal breast and salivary gland tissues (bNs and sNs, respectively) by quantitative real-time polymerase chain reaction on formalin-fixed paraffin embedded tissues. miRNAs showing significant differences between the study groups were selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…37 miR-199a was also up-regulated in malignant group tissue samples in our study. Recently Kiss et al 38 demonstrated possible role of down-regulation of miR-let-7b and miR-193b in salivary gland ACC pathogenesis. Again Kiss et al 39 found seven overexpressed miRNAs and nine down-expressed miRNAs in salivary ACC tissue samples in another study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 miR-199a was also up-regulated in malignant group tissue samples in our study. Recently Kiss et al 38 demonstrated possible role of down-regulation of miR-let-7b and miR-193b in salivary gland ACC pathogenesis. Again Kiss et al 39 found seven overexpressed miRNAs and nine down-expressed miRNAs in salivary ACC tissue samples in another study.…”
Section: Discussionmentioning
confidence: 99%
“… Kiss et al 39 2015 ACC ACC tissue samples were compared with normal salivary gland tissue 7 microRNAs were upregulated and 9 were downregulated. Kiss et al 38 2015 ACC ACC tissue samples were compared with normal salivary gland tissue miR-let-7b and miR-193b were down regulated in tissue samples Cinpolat et al a Benign and malignant SGTs (1) Comparison of saliva and serum samples between benign tumors, malign tumors and control group. (2) Comparison of tissue samples between benign and malignant SGT group.…”
Section: Discussionmentioning
confidence: 99%
“…miR‐27b and Gpr126 are both expressed during heart development and in endothelial cells, are both shear stress–regulated, and associated with cognitive impairment or intellectual disability, as well as bladder cancer . In addition, it is known that Gpr126 is expressed in the salivary gland, lung, and kidney, while miR‐27b is associated with non‐small cell lung cancer, clear cell renal cell cancer, and adenoid cystic carcinoma of the salivary glands . Moreover, miR‐27b has been shown to regulate the expression of delta‐like ligand 4 ( Dll4 ), which activates Notch signaling, an established regulatory pathway of Gpr126 expression in HUVECs and the endocardium of the developing heart …”
Section: Discussionmentioning
confidence: 99%
“…In an array‐based study of two breast and two salivary gland ACCs, Kiss et al. explored differences in miRNA expression, but were not able to reach significance and failed to confirm the findings in a subsequent study on a larger material . Discrepancies in studies on miRNA are well‐known, and the reasons for this are numerous and include differences in laboratory procedures, batch variation, detection hardware, intensity signal extraction algorithms, and bioinformatics analysis .…”
Section: Discussionmentioning
confidence: 99%